Eradication of wild poliovirus in Nigeria: Lessons learnt - Osmond C. Ekwebelem; Obinna V. Nnorom-Dike; Abdullahi Tunde Aborode; Nicholas C. Ekwebelem; Job C. Aleke; Ekenedirichukwu S. Ofielu (Elsevier, 2021)
Introduction: On August 24, 2020, Nigeria recorded a monumental success by achieving the aim of a "wild polio-free country" after completing three years without any case of wild poliovirus (WPV). Methods: For this commentary, we consulted relevant publications, official documents, and working plans and policy statements of the relevant organizations responsible for Nigeria's Polio Eradication Initiative. Results: Efforts to curb the challenges the Polio Eradication Initiative (PEI) faced in Nigeria through effective partnerships, the CORE Group Polio Project (CGPP), Volunteer Community Mobilizers (VCMs), and Global Polio Eradication Initiative (GPEI) partners proved successful, as it resulted in Nigeria being removed from the list of endemic countries in September 2015, and subsequently declared free of WPV on August 24, 2020, following an absence of indigenous transmission for three years. Conclusion: Unrelenting prioritization of polio eradication and global support is still needed to achieve a polio-free world.